Coal miner's daughter - Lynn, Loretta; Vecsey, George (Grand Central Publishing, 2022)
New York Times bestselling author and Nashville legend Loretta Lynn tells the story of her rise from deep poverty in Butcher Holler, Kentucky, to the top of the male-dominated country music industry -- now with new content. Reissued for the 40th Anniversary of the Oscar-winning, Sissy Spacek-starring film of the same name, Coal Miner's Daughter recounts Loretta Lynn's astonishing journey to become one of the original queens of country music. Loretta grew up dirt poor in the mountains of Kentucky, she was married at thirteen years old, and became a mother soon after. At the age of twenty-four, her husband, Doo, gave her a guitar as an anniversary present. Soon, she began penning songs and singing in front of honky-tonk audiences, and, through years of hard work, talent, and true grit, eventually made her way to Nashville, the Grand Ole Opry, eventually securing her place in country music history.